SOLID WASTE MANAGEMENT: A CASE OF LIBYA - Almukhtar Aljatlawe; Engin Baysen; Abdelrouf Ahmed Gbril Abdw (International Journal of Innovations in Engineering Research and Technology, 2023)
Solid waste is defined as the unwanted byproducts of human activities which can be in both commercial and domestic human activities. Solid waste can be very toxic and dangerous to human health if not adequately managed through various processes of what is known as solid waste management. Solid waste management is the process that is defined by the collection and treatment of solid waste to ensure the protection of both human and environmental health. Solid waste management is a process that is defined as crucial for public health and the individual health of the people in a society. Solid waste management is however a process that has significant challenges to be implemented adequately, especially in underdeveloped parts of the world. This study is a comprehensive investigation into the state of solid waste generation and the efforts of solid waste management in Libya; its challenges and efficiency, as well as the recommended processes for ensuring it is further improved.